A Shaking-Culture Method for Generating Bone Marrow Derived Mesenchymal Stromal/Stem Cell-Spheroids With Enhanced Multipotency in vitro - Niibe, Kunimichi; Ohori-Morita, Yumi; Zhang, Maolin; Mabuchi, Yo; Matsuzaki, Yumi; Egusa, Hiroshi (Frontiers in Bioengineering and Biotechnology, 2020)
Mesenchymal stromal/stem cells (MSCs), which generally expand into adherent monolayers, lose their proliferation and multilineage potential easily following repeated passages. Floating culture systems can be used to generate MSC-spheroids, which are expected to overcome limitations associated with conventional adherent cultures and to facilitate scaffold-free cell transplantation. However, the phenotypic characteristics of spheroids after long-term culture are unknown. In addition, regenerative therapies require new culture systems in order to maintain their undifferentiated state. In this study, we established a novel culture method employing three-dimensional (3D) "shaking" to generate MSC-spheroids using bone marrow derived MSCs. Floating 3D cultures of mouse or human MSCs formed spheroids after shaking (85-95 rpm), within one month.These spheroids maintained their osteogenic-, adipogenic-, and chondrogenicdifferentiation capacities. The adipogenic-differentiation capacity of adherent cultured mouse and human MSCs, which is lost following several passages, was remarkedly restored by shaking-culture. Notably, human MSC-spheroids showed a renewable "undifferentiated MSC-pool" property, wherein undifferentiated MSCs grew from spheroids seeded repeatedly on a plastic culture dish. These data suggest that the shakingculture method maintains and restores multipotency that is lost following monolayer expansion and thereby shows potential as a promising strategy for regenerative therapies with mesenchymal tissues.